Biological compatibility of some types of endodontic calcium hydroxide and glass ionomer cements - Valera, Marcia Carneiro [UNESP]; Leonardo, Mário Roberto; Consolaro, Alberto; Matuda, Fábio da Silva (Journal Of Applied Oral Science : Revista Fob, 2004)
The purpose of this work was to evaluate the biological compatibility of the Sealapex, Apexit, Sealer 26 and Ketac Endo endodontic cements. Polyethylene tubes containing these cements were implanted in the subcutaneous tissue of 40 (forty) rats. The animals were sacrificed after 14 and 90 days. A descriptive analysis of the reactions found in the connective tissue by contact with the cements was performed. The magnitude of inflammatory infiltrate, the presence and predominance of cell types and their distribution as to the filling material and reparative phenomena, such as fibroblastic and angioblastic proliferation and formation of fibrous capsules, were subjectively measured. After 90 days, all cements presented statistically significant reduction of the inflammatory reaction, presence of a fibrous tissue capsule in contact with the opening of the tubes containing the filling materials, and reduction of fibroblastic proliferation. Angioblastic proliferation decreased only for the Sealer 26 and Ketac Endo groups. All cements tested were either partially or totally phagocyted, and the mildest inflammatory response was found for the Sealer 26 group at both evaluation periods.

O objetivo deste trabalho foi avaliar a biocompatibilidade dos cimentos endodônticos Sealapex, Apexit, Sealer 26 e Ketac Endo. Para isto, tubos de polietileno preenchidos com os quatros tipos de cimentos endodônticos foram implantados no tecido conjuntivo subcutâneo de 40 ratos. Os animais foram sacrificados após 14 e 90 dias. Primeiramente foi realizada a análise descritiva das reações encontradas no tecido conjuntivo em contato com os cimentos. A magnitude do infiltrado inflamatório, a presença e predominância de tipos celulares e sua distribuição com relação ao cimento empregado, os fenômenos reparativos, tais como proliferação angioblástica e fibroblástica e formação de cápsula fibrosa também foram subjetivamente quantificados. A análise dos resultados mostraram estatisticamente que todos os cimentos apresentaram após 90 dias redução de reação inflamatória, formação de cápsula fibrosa em contato com a abertura do tubo que continha o material de preenchimento e redução na proliferação fibroblástica. A proliferação angioblástica estava reduzida somente no grupo dos cimentos Sealer 26 e Ketac Endo. Todos os cimentos foram parcialmente ou totalmente fagocitados e a menor resposta inflamatória foi encontrada no grupo do cimento Sealer 26 em ambos períodos de avaliação.
Biocompatibilidade de alguns tipos de cimento endodôntico à base de hidróxido de cálcio e cimentos de ionômero de vidro
Keywords: Endodontic cements; Calcium hydroxide; Biocompatibility; Glass ionomer cements; Cimentos endodônticos; Hidróxido de cálcio; Biocompatibilidade; Cimentos de ionômero de vidro